Study on Equatorial Bubbles Detected by SPS IMS Onboard the Kompsat-I - Jaejeung Park; Jaejin Lee; Ensang Lee; Kyoung-Wook Min (Journal of Astronomy and Space Sciences, 2002)
Space Physics Sensor onboard the KOMPSAT-1, which was launched at 1999, had transmitted ionospheric data during the solar maximum from June 2000 to August 2001. When the KOMPSAT-1 has passed the equatorial region, equatorial bubbles, in which the electron density abruptly decreases, had frequently been detected. Statistical analysis of the data obtained during the entire operational period shows equatorial bubbles frequently occur across the Atlantic region where the geomagnetic field strength is weak. Also, equatorial bubbles occur more frequently for lower Kp index. The results are in good agreement with the previous observations by DMSP satellites and radio experiments at the Peruvian sector. The correlation between electron density and the electron temperature shows various behaviors from event to event.